Respuesta :

EXPLANATION

The reason is that

[tex]i^2=-1[/tex]


If we multiply [tex]a+bi[/tex] by its conjugate [tex]a-bi[/tex]


We obtain;


[tex](a+bi)(a-bi)[/tex]

This is difference of two squares so we obtain;


[tex](a+bi)(a-bi)=a^2-(bi)^2[/tex]


This further gives us,

[tex](a+bi)(a-bi)=a^2-b^2i^2[/tex]

Since the [tex]i^2=-1[/tex], we substite to get;

[tex](a+bi)(a-bi)=a^2-b^2(-1)[/tex]

The [tex]i[/tex] is now eliminated and we get,


[tex](a+bi)(a-bi)=a^2+b^2[/tex]






ACCESS MORE